Aksiologi Pendidikan Islam (Nilai Moderasi Pendidikan Karakter dalam Primbon Serat MBonang) - Waluyo, Waluyo; Triwibowo, Agus; Al Fajri, Muhammad; Dardiri, Muhammad Amiruddin; Supriyanto; Alif Utama, Mohamad Maulidin Alif Utama (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Serat Mbonang is a classical Javanese religious manuscript attributed to Sunan Bonang that contains teachings on theosophy, theology, kalam, and Sufism. Although previous studies have examined its doctrinal and metaphysical aspects, limited research has explored its axiological structure and its relevance for contemporary Islamic character education. This study aims to address this gap by analyzing the integration of divine and human values in Serat Mbonang through the lens of Islamic educational axiology. The research employs a qualitative descriptive design using library data. Primary data consist of the Serat Mbonang manuscript, while secondary data include scholarly works on Nusantara religious literature, Sufism, and Islamic educational philosophy. Data were analyzed through textual analysis, interpretative reading, and axiological categorization supported by hermeneutic interpretation. The findings show, first, that Serat Mbonang constructs a coherent value system in which tawhid, spiritual discipline, and ethical conduct are presented as mutually reinforcing principles. Second, the manuscript embeds character education through aesthetic and cultural expressions, demonstrating the pedagogical role of art in Walisongo traditions. Third, the text offers an integrated model of value formation that rejects the dichotomy between divine and human values. These findings imply that Serat Mbonang provides a culturally grounded framework for Islamic character education relevant to modern contexts. The study concludes by recommending the integration of local wisdom-based manuscripts into contemporary educational models to strengthen value-oriented learning.